2014
DOI: 10.12707/riv14018
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of the Wong-Baker Faces Pain Rating Scale: linearity, discriminability and amplitude

Abstract: Enquadramento: As medidas de autorrelato da intensidade da dor são frequentemente tratadas como de nível de intervalo, um pressuposto raras vezes testado. Objetivos: Investigar o grau em que a Wong-Baker FACES Pain Rating Scale (FACES) apresenta propriedades de intervalo em amostras de crianças com diferentes idades (6-8; 9-11 anos) e experiências de dor. Metodologia: O estudo assenta na metodologia da Medida Funcional. Esta técnica oferece um critério empírico de validação da linearidade da resposta e a possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
0
16
0
9
Order By: Relevance
“…In several studies analyses of other pain measurement tools found evidence for and against an interval scale of measurements (e.g. Oliveira et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies analyses of other pain measurement tools found evidence for and against an interval scale of measurements (e.g. Oliveira et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate pain, the Wong-Baker Faces Scale (FACES) was administrated (Wong and Baker 1988). Studies have shown strong psychometric qualities (Stinson et al 2006), including in Portugal (Oliveira et al 2014). The scale has six faces representing pain intensity ranging from 0 (smiling face/not hurting) to 5 (crying face/hurts the worst).…”
mentioning
confidence: 99%
“…this will take into account differences in the properties of the primary outcome by age, with the score tending to linearity in those around eight years onwards, but behaving non-linearly for those under eight years. 25 furthermore, there is a discontinuity within the secondary outcome instruments, i.e. self-reports for those ≥ eight years old, and proxy-reports for those < eight years old for secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…the magnitude of pain within the intervals is not uniform), with non-linearity more likely in younger age-groups, tending to linearity in those over eight years old. 25 We therefore have powered the trial for equivalence separately in the two subpopulations (< eight years of age and ≥ eight years age), which is also important for secondary outcomes where some are proxy-reported for participants less than eight years and patient-reported for eight years and above. therefore, the trial is powered separately for equivalence in the two sub-populations (four to seven-year-olds and eight to 15-year-olds).…”
Section: Sample Sizementioning
confidence: 99%